Determination of Consumer Color and Discoloration Thresholds for Purchase of Retail Ground Beef When Evaluating Multiple Days of Display Simultaneously - K. R. Lybarger; E. S. Beyer; K. J. Farmer; L. A. Egger; L. N. Drey; J. L. Vipham; M. D. Zumbaugh; M. D. Chao; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to identify the threshold for color and discoloration for consumers to purchase ground beef in a simulated retail display and to determine the best objective measurement to predict consumer purchase intent. Study Description:For this study, 180 1-lb 80% lean/20% fat ground beef packages were assigned to a day of retail display (day 0–9). Consumers (n = 216) and trained descriptive panelists evaluated ground beef samples from each day of display simultaneously. InstrumentalL*(lightness), a*(redness),andb*(yellowness) values were collected, and spectral data were recorded. Logistic and simple linear regression models were calculated for consumer likelihood to purchase and appearance ratings. Pearson correlation coefficients were calculated for all measurements. The Bottom Line:The models generated from this study provide the ability to predict consumer willingness to purchase ground beef of varying days of retail display and provide ground beef producers an indication of potential consumer purchasing behaviors based upon objective values that are easy to measure.
Keywords: consumer; color; ground beef